2008
DOI: 10.1111/j.1750-3841.2007.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Functional Properties of Bovine Serum Albumin through Phosphorylation by Dry‐Heating in the Presence of Pyrophosphate

Abstract: Bovine serum albumin (BSA) was phosphorylated by 2 methods. One is dry-heating in the presence of pyrophosphate, and the other is conjugation with maltopentaose through the Maillard reaction and subsequent dry-heating in the presence of pyrophosphate. The phosphorus content of BSA was increased to approximately 0.45% by dry-heating at pH 4.0 and 85 degrees C for 5 d in the presence of pyrophosphate, and approximately 0.91% by glycation and subsequent phosphorylation. The circular dichroism spectra showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Due to the more digestible property of PP-EWP than the native one by proteases, the reduced antigenicity of PP-EWP may be expected after ingestion. Enomoto et al (2007Enomoto et al ( , 2008 and Enomoto, Hayashi, et al (2009) reported that the antigenicity of b-Lg and a-La was somewhat reduced by phosphorylation, and that of BSA was reduced significantly by phosphorylation. The reason for this difference is not clear.…”
Section: In Vitro Physiological Functions Of Pp-proteinsmentioning
confidence: 96%
“…Due to the more digestible property of PP-EWP than the native one by proteases, the reduced antigenicity of PP-EWP may be expected after ingestion. Enomoto et al (2007Enomoto et al ( , 2008 and Enomoto, Hayashi, et al (2009) reported that the antigenicity of b-Lg and a-La was somewhat reduced by phosphorylation, and that of BSA was reduced significantly by phosphorylation. The reason for this difference is not clear.…”
Section: In Vitro Physiological Functions Of Pp-proteinsmentioning
confidence: 96%
“…However, whey protein isolate showed a lower phosphorylation level than egg white protein by dry-heating under the same conditions, presumably due to the absence of a carbohydrate chain (Li et al, 2003). So, we attempted to phosphorylate whey protein isolate by glycation with maltopentaose through the Maillard reaction and subsequent dry-heating in the presence of pyrophosphate, with the results that whey proteins were effectively phosphorylated and some functional properties were improved by phosphorylation after glycation (Enomoto et al, 2007(Enomoto et al, , 2008(Enomoto et al, , 2009aLi, Enomoto, Ohki, Ohtomo, & Aoki, 2005a). Furthermore, these two methods of phosphorylation by dry-heating in the presence of pyrophosphate are simple and easily put to practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used this method for intrinsic fluorescence with excitation at 280 nm and scanning emission from 300-450 nm (Anand et al, 1998;Enomoto et al, 2008;Marangoni et al, 2000). Peak emission for whey protein is usually at 340nm (Anand et al, 1998).…”
Section: Analytical Quantification Of Whey Protein Denaturationmentioning
confidence: 99%
“…However, this is likely due to a lower total protein content in the whey obtained by centrifugal isolation than due a higher degree of isolation. In several studies when native PAGE has been used characterize whey protein denaturation, it is generally a part of a larger scope of gel electrophoresis methods including SDS-PAGE under reducing and/or non-reducing conditions and 2-dimentional PAGE, which allows for subjective comparisons between native and total protein content (Hong and Creamer, 2002;Considine et al, 2007;Chen et al, 2005;Enomoto et al, 2008;Havea et al, 2001;Anand et al, 1998). As previously discussed, the inherent differences from gel to gel and denaturing effects of other PAGE methods make it unrealistic to make such comparisons quantitatively.…”
Section: Characterization Of Native Whey Proteinmentioning
confidence: 99%
See 1 more Smart Citation